2022
DOI: 10.1111/jonm.13597
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effect of nurse managers' toxic leadership behaviours on nurses' perceptions of professional values: A cross‐sectional survey

Abstract: Aim This study aimed to investigate whether or not the toxic leadership behaviours of nurse managers influence nurses' perceptions of professional values. Background Professional values are among the factors that influence the development and the enhancement of the quality of health services. The professional development of nurses at work is particularly shaped by the guidance and counselling of nurse managers. Therefore, it is vitally important to determine the effects of nurse managers' toxic leadership beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The nurses in the current study perceived the nature of nurse managers' behaviours as moderately toxic. Though Lavoie‐Tremblay et al (2016) and Labrague (2021) reported opposing findings among nurse managers, the report by Abou‐Ramadan and Eid (2020) and Özkan et al (2022) in Egypt and Turkey, respectively, were consistent with the study findings. It is worth noting that effective leadership behaviour in addition to trust, mutual respect, and honest communication between nurse managers and subordinates are important for maintaining a professional practice environment with positive outcomes of safe and quality care, work engagement, job satisfaction, and increased productivity in the organization (Alkassabi et al, 2018; Field & Brown, 2019; Lei et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…The nurses in the current study perceived the nature of nurse managers' behaviours as moderately toxic. Though Lavoie‐Tremblay et al (2016) and Labrague (2021) reported opposing findings among nurse managers, the report by Abou‐Ramadan and Eid (2020) and Özkan et al (2022) in Egypt and Turkey, respectively, were consistent with the study findings. It is worth noting that effective leadership behaviour in addition to trust, mutual respect, and honest communication between nurse managers and subordinates are important for maintaining a professional practice environment with positive outcomes of safe and quality care, work engagement, job satisfaction, and increased productivity in the organization (Alkassabi et al, 2018; Field & Brown, 2019; Lei et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
“…Other studies associated toxic leadership by nurse managers with reduced emotional intelligence (Abdallah and Mostafa, 2021) and increased use of conflict management styles such as avoiding, accommodating, competing and collaborating (Abou Ramadan and Eid, 2020). Toxic leadership had no significant effects on nurses’ professional values, as reported in one study (Özkan et al , 2022).…”
Section: Major Findingsmentioning
confidence: 59%
“…We attempted to ensure homogeneity in the samples by choosing equal sample sizes from public and private hospitals. However, when compared to previous studies, our sample was smaller than the sample sizes utilized by Labrague [ 33 ], who had a sample of 926 nurses working at 20 hospitals, but larger than the samples from Özkan et al [ 50 ], who investigated 244 nurses’ perceptions working at a university hospital, and Webster et al [ 32 ], who surveyed 14 health care workers. To ensure greater generalizability of the results, future research may consider larger samples and include other health care workers in addition to nurses.…”
Section: Discussionmentioning
confidence: 92%